WOMAN’S STATUS IN THE CREATION NARRATIVES IN THE QUR’AN AND TORAH - Sadatmoosavi, Zohreh; Wan Ali, Wan Zailan Kamaruddin; Shokouhi, Mohammad Ali (Jurnal Syariah, 2017)
Women have played various roles in all cultures throughout time. However, the Qur’an and Torah have explicated the specific role of women in their creation narratives. In particular, the story of Adam and Eve’s creation and their fall from grace after consuming the fruit from the Forbidden Tree are depicted in both holy books. There are some resemblances in this story between the Qur’an and Torah, but some significant differences as well. For instance, the Torah considers that Eve was created from Adam and seduced him to eat from the tree, thereby taking chief responsibility. However, the Qur’an states that God has created man and woman from a single soul (person) in order that they dwell in love, placing equal blame on both. Moreover, the Qur’an notes that they repented from their sin and God forgave them. Due to the Torah’s significantly more biased perspective, this has had a negative influence on some important social and religious values in Western civilization for nearly two thousand years. This comparative study can offer an essential perspective for redefining women’s dignity in the West and the superiority of the Quranic approach.